(3GdJbQjQGJs - (3GdcdHGSj GdfLaj, eMeO EHQGgje Hf MSjf GdcdHGSj GdfLaj, hdO SfI (B1322(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdeHMK GdKGfj aj GdfhGgj hajg eSGFd, GdChdi aj (B... (3Gdfgj hajgG LgGJ ef GdcdGe, GdLgI GdChdi ajgGs
(3BNQgG (B:s
(3BNQgG(B: (3aj GdeLed hGdeHjf hCaGO Cfg djS aj Jdc GdeHGMK (B... (3adfTQY aj GdCOdI GdYbdjI hdfNfe GdcdGe Ydi eHGMK GdCdaGXs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B4: 268s
(3GdPQjYI, L (B4: 268s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs